Un Modelo Logístico para Crecimiento Tumoral en Presencia de Células Asesinas - Ortega, H. (Revista Mexicana de Ingenieria Biomedica, 1999)
We study a modified Hiernaux-Lefever tumor model (1987) in order to include a variable killer cells population. We obtain a coupled two differential equations system with three independent parameters and several equilibria points. Tumor progression and regression depend on particular values of this parameter. We get an explanation to paradoxical situations generated by the common Hiernaux-Lefever model by using variable stability regions on an extended parameters space. The structure of these regions provides an elegant description of the tumor response to a given treatment.